The Peningkatan Keterampilan Pengembangan Website Studi Kasus SMK Taruna Warmadewa - Putu Maya Satya Nandira; Ni Kadek Anggita Putri; Ni Putu Septian Pramesti; I Wayan Bayu Tangkas Ariarta; Wichesa Iswarabhawa Ariarta; I Dewa Gede Agung Wahyu Brahmantha (WIDYABHAKTI Jurnal Ilmiah Populer, 2025)
In the digital era, internet use is increasingly widespread, including in education. Taruna Warmadewa Vocational School in Denpasar, Bali, seeks to improve students' information technology skills through socialization and basic training in website creation. Although most students already have a basic understanding of website concepts, training and outreach is still minimal. This activity aims to introduce students to the basic programming languages HTML and CSS, so that they can understand the initial process of creating a website. Training is carried out using direct practice methods using applications such as Visual Studio Code and Google Chrome. Students are guided to create a simple portfolio website as part of personal branding. The results of the training show that participants are able to create basic websites and understand the importance of websites in building a professional image in the digital world. It is hoped that similar training can continue to be carried out so that students have soft skills that are useful in developing their careers in the future.